PANDEMIC CHALLENGE: EVALUASI PEMBELAJARAN ONLINE MENGGUNAKAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) - Ni Kadek RIni Purwati; Ni Ketut Erawati (De Fermat : Jurnal Pendidikan Matematika, 2021)
Learning mathematics online is a challenge for teachers considering that mathematics has abstract characteristics. Therefore, online learning needs to be designed to be effective. This study aims to evaluate online learning in the Mathematics Education Study Program using Importance Performance Analysis (IPA). Sampling was carried out using random sampling techniques in each batch of students of the Mathematics Education Study Program, PGRI Mahadewa University, Indonesia. Based on the results of the analysis and discussion, it was found that online lectures had gone according to student expectations. This is shown from the results of the IPA, namely that most of the indicators are in Quadrant I with the label "Keep Up the Good Work".